Building Brand Loyalty Through Brand Image, Perceived Value, and Brand Trust: A Study of NBRS, an Indonesian Modest Fashion Brand - Al-ausath, Najmah Syahidah; Dalimunthe, Gallang Perdhana (Management Analysis Journal, 2025)
key factors in brand loyalty in NBRS, one of Indonesia's leading modest fashion brands, which is currently experiencing a decline in sales performance despite market growth. This contrast suggests that NBRS's market share losses were primarily due to brand-specific issues, particularly loyalty, rather than an overall market recession. Using a quantitative approach involving a structural equation modeling technique (SEM-PLS), based on a sample of 113 NBRS consumers, this study examines the roles of brand image, perceived value, and brand trust. The results show that brand image and perceived value positively influence brand loyalty, both directly and indirectly through brand trust. An internal analysis using a VRIO framework indicates that NBRS possesses strategic assets like a well-structured distribution network and partnership arrangement, while the external analysis using Porter's Five Forces Framework highlights high competition in the market, increasing threats from substitutes, and high bargaining power of buyers. Based on these insights, integrated marketing communication (IMC) strategies including digital advertising, sales promotions, public relations, experiential events, interactive content, and personal selling are recommended to improve the perceived value, brand image, and brand trust toward the brand loyalty.